Freshwater conservation planning under climate change: demonstrating proactive approaches for Australian Odonata. Issue 5 (24th June 2014) - Bush, Alex; Hermoso, Virgilio; Linke, Simon; Nipperess, David; Turak, Eren; Hughes, Lesley; Angeler, David
Summary Climate change represents a major challenge for conservation in the future and undermines protection within reserve boundaries. Freshwater biodiversity is still under‐represented within reserves world‐wide, and connectivity among reserves will become increasingly crucial if species are to persist under climate change. We tested the likely benefits of including predicted species distributions in systematic reserve design for rivers under climate change and the impact of varying connectivity requirements on future representation. We used the modelled distribution of 126 east Australian Odonata to identify reserve networks using data for current or future (2055 and 2085) distributions either by filling gaps additively, or as separate targets in a single solution. We then assessed the potential improvements to species representation in the future using different types of connectivity penalties that emphasized either longitudinal riverine connections or connections to all neighbouring subcatchments. Solutions that did not include future distributions in the planning stages were 16 to 30% less likely to protect the same species by 2055 and 2085, respectively. Inclusion of species' future distributions in the design phase leads to short‐term increases in cost, but in the longer term fewer additional areas are required to meet targets and this strategy is likely to be significantly more efficient than implementing systematic design in stages. In addition, solely targeting riverine connectivity was significantly less likely to protect current species in the future than if cross‐catchment connections were included. Synthesis and applications. Where protected areas can be expanded to assist species adaptation to climate change, significant gains in efficiency are possible if longer term goals are considered when selecting sites. Furthermore, to improve the representation of species under future climates, reserve selection should consider inter‐catchment connectivity, although the nature of optimal solutions will depend heavily on the range of taxa included, their dispersal capacity, and the availability of climatic refugia.